Knowledge Gap on Integrated Pest Management in Chumoukedima District, Nagaland - Pongen, N. I.; Longkumer, J.; Odyuo, M. N. (International Journal of Economic Plants, 2025)
The present study was carried out from December, 2022 to April, 2023 in Chümoukedima district of Nagaland with the aim of assessing farmers’ knowledge level on Integrated Pest Management (IPM) practices. A multistage random sampling method was used to select 100 farmers from five purposively selected villages under Dhansiripar block, an area known for its active farming community. Data were gathered through personal interviews using a carefully prepared set of questions, and the responses were later analyzed with the help of descriptive statistics like percentages, averages, and standard deviations. Correlation analysis was also done to find out how farmers’ backgrounds affected their knowledge of IPM. The results showed that every farmer knew about traditional practices such as summer ploughing, crop rotation, handpicking pests, and sieving stored grains. However, when it came to biological control methods and the use of plant-based pesticides, awareness dropped, with only 61% and 53% of respondents familiar with them, respectively. The overall Knowledge Index for IPM in the study was calculated at 83.29, and most farmers (77%) fell within a medium knowledge category. Knowledge showed significant positive correlation with age, education, occupation, and social participation. The study highlighted the need for more localized awareness programs, practical demonstrations, and farmer training sessions to bridge this knowledge gap and encourage wider adoption of sustainable pest management techniques in the region.